What does it mean to eat an appropriate amount of food?. (December 2016) - Vartanian, Lenny R.; Herman, C. Peter; Polivy, Janet
Abstract: Norms of appropriateness have been used to account for the influence of a variety of external eating cues (e.g., social factors, portion size) on people's food intake. What is less clear is what, exactly, "appropriate" means. This study explored participants' conceptions of appropriate food intake. Two separate samples were included in this study: 121 university students (73% women) and 107 community members (100% women). Participants were asked to rate the extent to which several statements reflected the concept of "appropriate food intake" or "normal food intake" (1 = Does not capture the definition at all ; 7 = Captures the definition perfectly ). These statements included items referring to external eating cues (e.g., "Eating as much as other people", "Eating the entire portion of what you are served") and items referring to internal eating cues (e.g., "Eating an amount that will make you feel satisfied") or nutritional needs (e.g., "Eating a healthy amount"). Repeated measures ANOVAs indicated that participants consistently defined appropriate/normal intake in terms of internal eating cues and nutritional needs. In contrast, despite evidence indicating that perceptions of how much is an appropriate amount to eat are affected by external eating cues, external eating cues were ignored in participants' definition of appropriate/normal intake. The disconnect between how people define appropriate intake (i.e., in terms of internal cues) and what research shows affects norms of appropriateness (i.e., external cues) may reflect people's general unwillingness to acknowledge the influence of external eating cues on their food intake. Highlights: External eating cues are through to provide a norm of appropriate intake. We examined participants' definitions of "appropriate intake" and "normal intake". Appropriate/normal intake were defined in terms of internal eating cues. Appropriate/normal intake were also defined in terms of nutritional needs. External eating cues were not included the definition of appropriate/normal intake.